Modulatory effects of organic acids on gastrointestinal health and immune response in poultry - Qazal Hina; Ishaya U. Gadzama (Bulgarian Journal of Animal Husbandry, 2026)
Antibiotics has been utilized in poultry production for centuries to enhance production rates. The inappropriate use of antibiotics has led to numerous problems, such as resistance to antibiotics, remnants in animal byproducts, and environmental pollution. Consequently, the European Food Safety Authority and European Union advocate for implementation of action plans to reduce the antibiotics usage in animal production. Acidic compounds consisting of organic acids (OAs) exhibit potential as alternatives to antibiotics. Organic acids have shown the ability to improve poultry performance by modifying the pH of the gastrointestinal tract (GIT), and so influencing the microbiome composition. Organic acids may strengthen the physiology and morphology of the GIT, hence providing protection to poultry birds. Moreover, dietary OA may influence cytokine levels in the host and enhance both humoral and cell-mediated immunity. The aim of this review is to elucidate the impact of OAs on the poultry microbiome and the subsequent influence of these alterations on pathogen proliferation and disease incidence in poultry. This review indicates that the effectiveness of OAs in altering microbiome composition is affected by the dosage, the specific formulation of the OA product, and the health and immune status of the poultry species, as a robust immune system closely interacts with gut microbiota and can influence the overall efficacy of OAs supplementation.